Mindset and Resilience: A Correlational Study in Senior High School 12th Grade Students - Putri, Nawangsari Indah Kusuma; Priyatama, Aditya Nanda (Universitas Negeri Surabaya, 2024)
Background: Senior high school students in the last academic year face increasingly high academic and social pressures. This increasing adversity level must be followed by high adaptation competence. Students must have the endurance to adapt positively in facing difficult situations, called resilience. Mindset influences students' responses and ways of facing challenges or adversities. However, few studies have explored the relationship between mindset and resilience. Objective: Aim to examine the correlation between mindset and resilience in 12th grade students in SMAN 5 Surakarta. Method: This study was conducted with 196 students from 12th grade in SMAN 5 Surakarta, obtained through simple random sampling in October 2023. Resilience was measured using the Resilience Scale (r=0.902) and mindset was measured using the Mindset Scale (r=0.801). To analyze the data, the assumption tests, Pearson’s correlation, descriptive statistics, and Independent Sample t-test were used. Results: Out of the total data from 196 students, only 190 students met the criteria to continue. The data obtained was proven to have a normal distribution and a linear correlation. Then, the finding of Pearson’s correlation was shown that mindset and resilience have a significant positive relationship (r=0.372; p<0.05). The relationship that occurs is relatively low and mindset determines resilience by 13.8% (r²=0.138). The findings also revealed that male students have higher resilience than female students (Mdifference= 3.478; p<0.05). Conclusion: The results of this study imply that the more students have a growth mindset, the higher their resilience. Abstrak Latar Belakang: Siswa yang berada dalam tahun terakhir di SMA menghadapi tuntutan akademik dan sosial yang semakin tinggi. Tantangan yang semakin meningkat ini harus diikuti oleh kompetensi adaptasi yang tinggi. Siswa harus memiliki daya tahan untuk beradaptasi secara positif dalam menghadapi situasi sulit atau disebut resiliensi. Mindset mampu memengaruhi respons dan cara siswa dalam menghadapi tantangan ataupun kesulitan. Namun, penelitian tentang korelasi antara mindset dengan resiliensi masih terbatas. Tujuan: Untuk mengetahui hubungan antara mindset dengan resiliensi pada siswa kelas XII SMAN 5 Surakarta. Metode: Penelitian ini melibatkan 190 siswa kelas XII SMAN 5 Surakarta yang diperoleh melalui simple random sampling pada Oktober 2023. Resiliensi diukur menggunakan Skala Resiliensi (r=0.902) dan mindset diukur dengan Skala Mindset (r=0.801). Analisis data dilakukan dengan uji asumsi dasar, korelasi Pearson, statistik deskriptif, dan Independent Sample t-test. Hasil: Dari 196 data terkumpul, hanya 190 data yang bisa dilanjutkan untuk dianalisis. Data terbukti memenuhi syarat normalitas dan linearitas. Berdasarkan uji korelasi product moment Pearson, dibuktikan bahwa mindset dan resiliensi memiliki hubungan positif yang signifikan (r=0.372; p<0.05). Hubungan yang terjadi tergolong rendah dan mindset menentukan resiliensi sebesar 13.8% (r²=0.138). Hasil penelitian juga menemukan bahwa siswa laki-laki memiliki resiliensi yang lebih tinggi daripada siswa perempuan (Mdifference= 3.478; p<0.05). Kesimpulan: hasil penelitian ini menunjukkan bahwa semakin siswa memiliki growth mindset, semakin tinggi resiliensi siswa.